REVISITING ISLAMIC ENVIRONMENTAL ETHICS FOR SUSTAINABLE ECONOMICS - Santo Hartono, Haryani (AL-IQTISHAD : Jurnal Perbankan Syariah dan Ekonomi Islam, 2025)
The paper examines how Islamic-based environmental ethics can be incorporated into sustainable economic systems through re-examination of the ethical aspect of human attitude towards nature as expounded by Ibrahim Özdemir. It claims that the contemporary Islamic economic practices have not taken into consideration much of the ecological nature of maqasid al-shariah, but rather on financial and institutional processes. Through a qualitative, interpretive method based on textual analysis and theoretical synthesis, the paper uses the principles of maqasid, tawhid, mizan, khilafah, and amanah to make a connection between the moral responsibility and ecological balance on the one hand and the socio-economic goals on the other hand. The results suggest that sustainability can be theorized as a value model in which the concept of sustainability can be viewed as a state where the balance between the material well-being, social justice, and environmental balance is reached, that is, a state of falah, holistic falah. It also proposes operational uses like green sukuk, eco-waqf and environmental zakat to incorporate ecological ethics in the Islamic finance. The paper concludes that divine ethics in the economy is a sure way to have a spiritually based and ecologically sound system of sustainable development.